[Manuscript Correction]-Indonesia’s Palm Oil Plantation Regulations for Promoting Community Protection and Justice - Dedi Wahyudi; Bambang Tri Bawono; Bahtiyar Efendi (Contrarius, 2026)
The expansion of palm oil plantations in Indonesia has generated complex legal issues related to community protection around Cultivation Rights areas, land tenure conflicts, and the effectiveness of justice mechanisms in natural resource governance. Although agrarian, plantation, environmental, and human rights regulations formally recognise community protection, empirical evidence shows recurring agrarian conflicts and unequal benefit distribution. This study aims to: (1) analyse legal instruments governing community protection in palm oil plantation management; (2) evaluate the effectiveness of justice mechanisms and the role of state institutions in regulatory enforcement; and (3) formulate justice-based regulatory reconstruction through an international comparative approach. This research applies an empirical juridical method with a socio-legal approach, combining statutory analysis and fieldwork conducted in the operational areas of PT Agri Andalas, PT Bio Nusantara Teknologi, and PT Pamor Ganda in Bengkulu Province. The analysis applies Rawl’s distributive justice, the social function of land rights, and law as social engineering. The findings show that Indonesia faces a legal gap between regulation and implementation, marked by administrative legality dominance, fragmented institutions, and procedural participation. Although justice mechanisms formally exist, unequal access limits the availability of substantive remedies. Comparative insights from the Netherlands, Canada, and Norway emphasise integrated governance, binding community consent, transparency, and restorative grievance systems. Strengthening community protection, therefore, requires shifting from administrative legality toward social legitimacy and distributive justice through institutional integration and stronger enforcement.